Misleading Morphologic and Phenotypic Features (Transdifferentiation) in Solitary Fibrous Tumor of the Head and Neck: Report of 3 Cases and Review of the Literature - Baněčková, Martina; Michal, Michael; Hájkova, Veronika; Haller, Florian; Mosaieby, Elaheh; Salajka, Pavel; Arolt, Christoph; Nachtsheim, Lisa; Michal, Michal; Agaimy, Abbas; Skálová, Alena (The American journal of surgical pathology, 2022)
Solitary fibrous tumor (SFT) is a rare fibroblastic neoplasm with potentially malignant behavior that may develop in any anatomic site and may involve the head and neck (H&N) region as well. Although typical SFT has a relatively characteristic morphology, its morphologic spectrum is extraordinarily broad and also includes rare cases with dedifferentiation or transdifferentiation which result in aberrant morphologic and/or immunohistochemical features. However, since virtually all cases are molecularly characterized by NAB2::STAT6 gene fusions, molecular genetic methods or STAT6 immunohistochemistry can be effectively used in confirming the diagnosis. Herein, we report 3 diagnostically challenging H&N SFT cases with an unusual morphology and/or phenotypes closely mimicking other well-known H&N entities. The tumors originated in the oral minor salivary glands, the base of the tongue, and sinonasal tract and closely resembled hyalinizing clear cell carcinoma of the salivary gland, adenocarcinoma not otherwise specified and biphenotypic sinonasal sarcoma, respectively. All cases were positive for cytokeratins, variably expressed S100 protein, showed diffuse nuclear STAT6 positivity, and harbored NAB2::STAT6 gene fusions.
Keywords: Biomarkers, Tumor; Head and Neck Neoplasms; nádorové biomarkery; transkripční faktor STAT6; solitární fibrózní tumory; Solitary Fibrous Tumors; Phenotype; transdiferenciace buněk; Humans; Repressor Proteins; STAT6 Transcription Factor; lidé; Cell Transdifferentiation; fenotyp; represorové proteiny; nádory hlavy a krku